INTERRELATION OF FLOW EXPERIENCE WITH INTRINSIC MOTIVATION AND PERSONALITY TRAITS IN STUDENTS - Volk, M.I.; Savelieva, D.I. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2017)
The study examines the experience of “flow” in its relationship with the motivation and individuality of students. The flow pattern is clarified by the analyses of presence of elements related to motivation. The article discusses different approaches to the determination of flow-state within holistic and causal directions, provides an overview of the problematic points of this concept and raises the question of the considering the elements traditionally identified as the part of flow as elements of motivation. The empirical study involved 133 university students of 1-3-years of study. The Russian version of the questionnaire “The flow state scale-2” in the author’s adaptation (D. I. Savelieva), the “academic motivation scale” (T. O. Gordeeva, O. Sychev, E. N. Osin) and the H. Eysenck questionnaire G-EPQ (extroversion-introversion and neuroticism-emotional stability scales) were used. The result of correlation and factor analysis revealed significant relationships of most of the “flow”-elements with motivation to learn (especially with intrinsic motivation). At the same time, it is established that extraversion-introversion is associated only with two elements of “flow” (a clear goal and loss of consciousness), and neuroticism-emotional stability with one (loss of consciousness). An attempt to identify at the empirical level the “flow” elements, matching the theoretical description of motivation has failed. The theoretical reasons of the obtained results, of the relationship of flow, motivation to learn, and individual students’ personal characteristics are discussed.